2019
DOI: 10.1016/j.tig.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Tools To Live By: Bacterial DNA Structures Illuminate Cancer

Abstract: Holliday junctions (HJs) are DNA intermediates in homology-directed DNA repair, and replication stalling, but until recently, were undetectable in living cells. We review how an engineered protein that traps and labels HJs in Escherichia coli illuminates DNA biology and cancer. HJ ChIP-seq showed directionality of double-strand-break (DSB) repair in the E. coli genome. Quantification of HJs as fluorescent foci in live cells revealed that the commonest spontaneous problem repaired via HJs is replication-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…RDG binds and traps HJs specifically (schematic in Fig. 1B) in living cells and as a purified protein (5,10). We find that spontaneous X-seq signal is highest near the replication terminus region (Ter), where it forms three discrete peaks that span approximately 300 kb of the 4.6-Mb genome (Fig.…”
Section: Hj Map Reveals Fragile Sitesmentioning
confidence: 90%
See 1 more Smart Citation
“…RDG binds and traps HJs specifically (schematic in Fig. 1B) in living cells and as a purified protein (5,10). We find that spontaneous X-seq signal is highest near the replication terminus region (Ter), where it forms three discrete peaks that span approximately 300 kb of the 4.6-Mb genome (Fig.…”
Section: Hj Map Reveals Fragile Sitesmentioning
confidence: 90%
“…The high sensitivity of RDG results from its trapping nature, which allows accumulation of HJs by preventing their further chemistry, both biochemically and in cells (5). Similar DNA structure-trapping proteins identify DSBs in human and bacterial cells (40), and DSBs plus another DNA damage structure(s) in bacteria (10,41). HJ-trapping reagent(s) for human cells might improve detection of fragile sites and aid definition of their mechanisms of fragility.…”
Section: Discussionmentioning
confidence: 99%
“…RSC Chemical Biology junction (a crucial intermediate during HR repair of both DSBs and replication-dependent ssDNA gaps, as demonstrated by live cell imaging and HJ-ChIP-seq), 405,406 thus abrogating the action of Holliday junction-processing enzymes by displacing RecG helicase and inhibiting RuvABC resolvase, in the case of WRWYCR, for which the active form is the disulfide-bridged dimer (Fig. 9e).…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, experiments in E. coli performed with an engineered synthetic protein that traps Holliday junctions have revealed that most spontaneous recombination events arise from the repair of ssDNA gaps originated during DNA replication rather than from the repair of DSBs [47]. This is likely the case in other organisms, what points to ssDNA gaps caused by replication as a major source for tumorigenesis [48], and hence, opens the possibility that DNA-RNA hybridization at such gaps has a role in cancer origin. The initial lesions leading to such ssDNA gaps could be different sorts of DNA damage or replication stalling agents, among which DNA-RNA hybrids themselves are included ( Figure 3).…”
Section: Dna-rna Hybrids At Postreplicative Ssdna Gapsmentioning
confidence: 99%